The impact of global value chains on wages, employment, and productivity: A survey of theoretical approaches - Sabina Szymczak (Journal for Labour Market Research, 2024)
This study presents a systematic literature review to provide a collection of theories explaining the impact of global value chains (GVCs) on labour market outcomes. Due to the complex nature of GVCs and the interconnectedness of wages, employment, and productivity, many direct and indirect effects are at play. To ensure a transparent and systematic flow of the review process, I follow the PRISMA guide. Eventually, 36 records out of 1221 results from Scopus database were selected. This review may be useful for theorists, empirical economists, and policy makers as an overview of theoretical developments and convenient map of potential outcomes expected from involvement in GVCs. It identifies and systematizes a number of effects existing in the literature under various names. The results show that the predictions from the theory are ambiguous. The positive effects which may emerge regardless the characteristics of the GVC are the productivity-enhancing effect and the cross-effect, especially important considering growing servicification of manufacturing. Here lies the critical role of the state and policies to assure that the losses will not exceed the gains in the aggregate terms. One of the main factors shaping the outcome is the power distribution among the GVC's firms. Additionally, this paper shows the shortcomings of the existing theories. Less aggregated levels of analysis could be a great input to the discussion, as well as addressing different GVCs' dimensions and types of organisation. The understanding of relation between GVC position and labour market is especially worth exploration as the existing evidence adopt different and even contradicting perspectives on the definition of upgrading the GVC position.
Keywords: F16; F60; 330; Employment; Wage; Productivity; Systematic literature review; Global value chains